Cycle of Rasul Gamzatov’s Poems about Georgia (Proceedings of Southern Federal University. Philology, 2020)
The cycle of Rasul Gamzatov’s poems about Georgia attracts the attention of readers and researchers with colorful images, expressiveness, optimism and love of life, sparkling in these works. The international spirit of friendship and brotherhood of the Dagestan and Georgian peoples, who have much in common in the historical, cultural, political and socioeconomic spheres, is traced through all these poems. The works of this cycle reveal the subject and natural world of Georgia, the mentality of its people, the images of bright figures of literature and art, they express the love and respect that he kept in his heart. The article defines the main motives, means of expression in poems about Georgia, their genre, ideological and thematic characteristics.Key words: Georgia, friendship and brotherhood, Georgian women, beauty, landscape, lyrics, emotional pathos, sadness, metaphor.DOI 10.18522/1995-0640-2020-1-146-155